EL PROFESOR COMO PERSONA SIGNIFICATIVA: la diferencia entre la percepción de los alumnos de gimnazjum con problemas de aprendizaje y sin ellos - Ewa Domalaga-Zysk (Fundación San Pablo Andalucia CEU, 2019)
The paper shows the importance of social and school support from the adolescents' teachers in the process of doing well at school. In the research project the main focus was to find correlations between the quality of the relationship with teachers and the school success or school failure, which was measured by students' average grades. The results of the paper and pencil survey programm, based on and Hendry's (1992) and Tatar's (1996) techniques shows that students experiencing school failure differ from those with school success in the quality of the relationship with teachers. Adolescents with school success more often perceive their teachers as enablers, helpers, motivators, role models or supporters. For the students with school failure teachers were more often significant in the negative way, as bullies or antagonists. The conclusion is that in order to help teenagers to achieve school success pedagogues should not only teach academic skills, but create and support good relations with them.